(untitled) (Journal of the College of Basic Education, 2023)
This research is an attempt to reveal a grammatical personality, which is (Ibrahim bin Muhammad bin Ibrahim bin Ishaq bin Isa bin Asbagh Al-Baji), who died in the year 350 AH. Many of his opinions, quotes, and grammatical preponderances were conveyed by the grammarians who came after him, especially Abu Hayyan Al-Andalusi (d. 745 AH). More than five scholars participated in it, then we investigated some of the grammar issues that were reported from him in the works of those who came after him, and we stopped at some of them and did not show them all, and perhaps this research in its haste opens the door and paves the way for a serious academic study of this linguist . Finally we can say ;the grammarian Ibn Asbagh had some opinions that were agreed upon by most of the Basrans. We learned about them through his transmission from the grammarians who came after him. Ibn Asbagh transmitted in those restaurants, such quotes, and the quotes are identical to what they have from scholars.